Endoscopic Transcolonic Catheter-Free Pelvic Abscess Drainage. (2008) - Alis, Halil; Soylu, Aliye; Dolay, Kemal; Aygun, Ersan
Abstract : Natural orifice transluminal endoscopic surgery is a novel therapeutic method in development that uses different routes of surgical approach. The use of various methods, instruments and accessories during this procedure are currently being investigated. A case of appendicitis-related intra-abdominal abscess that was resolved by a transcolonic endoscopic approach using a wide-channel colonoscope with the help of precut and standard sphincterotome without radiological percutaneous drainage is presented.